Kontrol Orang Tua terhadap Remaja di Lingkungan Tempat Tinggal Berisiko Tinggi di Kota Pekanbaru - Rahmad Saputra; Rina Susanti (Pusat Riset dan Inovasi Nasional, 2025)
Parental control over adolescents in this study was conducted in high-risk residential environment where massage parlors with additional services are present. This study aims to determine the driving factors and level of parental control implementation among adolescents in the residential environment using Travis Hirschi's social control theory approach. The data analysis used in this study is descriptive quantitative research. The population consisted of all parents with adolescents aged 15-21 years, totaling 46 families. The entire population was used as samples using census sample technique. Data was collected through questionnaire completion, and central tendency calculations. The research results show that knowledge anda perseption factors have a strong connection to the level of parental control implementation among adolescents in high-risk residential environments in terms of attachment, commitment dan belief aspects. However, the aspect of parential involvement in accompanying adolescents is still relatively moderate thus requiring improvement.